Predictors of Ophthalmic Manifestations in Patients with Ankylosing Spondylitis - Daria A. Karpova; Maria N. Ponomareva; Ivan M. Petrov; Sergey M. Klyashev; Yulia M. Klyasheva; Polina A. Luntovskaya (International Journal of Biomedicine, 2022)
The aim of this study was to conduct a clinical and statistical analysis of ophthalmological manifestations in patients with Ankylosing Spondylitis (AS) using biologic disease-modifying antirheumatic drugs (bDMARDs) as a basic therapy. The study included 58 patients (19[32.7%] women and 39[67.3%] men) with AS receiving bDMARDs. The median age of patients was 41.81(25;60) years. The average age of the disease onset was 25.23(9;47) years. The patients were divided into two groups: Group 1 included 24 patients with ophthalmic manifestations; Group 2 included 34 patients without ophthalmic manifestations. All patients in Group 1 took TNF-α inhibitors, (infliximab, adalimumab, golimumab, etarnacept, and cetrolizumab-pegol). In Group 2, TNF-α inhibitors (infliximab, adalimumab, golimumab, etarnacept) were received by 32(92.4%) patients and interleukin-17 inhibitor (secukinumab) by 2(5.8%) patients. Group 1 was characterized by a greater age and average duration of the disease, as well as the presence of metabolic instability (blood glucose and creatinine levels in the borderline range). The effectiveness of bDMARD in AS is characterized by the normalization and stabilization of clinical and biochemical parameters, including blood cholesterol and creatinine levels, which prevents the occurrence of vascular lesions, including uveitis.